Impact of the COVID-19 pandemic on audiology services in South Africa: A preliminary study - Katerina Ehlert (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences, 2023)
Background: Hygiene-, work practices, travel, personal interactions and access to healthcare services changed for the majority of the world during the pandemic.